2017
DOI: 10.1186/s13041-017-0300-4
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis patient iPSC-derived astrocytes impair autophagy via non-cell autonomous mechanisms

Abstract: Amyotrophic lateral sclerosis, a devastating neurodegenerative disease, is characterized by the progressive loss of motor neurons and the accumulation of misfolded protein aggregates. The latter suggests impaired proteostasis may be a key factor in disease pathogenesis, though the underlying mechanisms leading to the accumulation of aggregates is unclear. Further, recent studies have indicated that motor neuron cell death may be mediated by astrocytes. Herein we demonstrate that ALS patient iPSC-derived astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 48 publications
6
89
0
Order By: Relevance
“…Using a fully humanized, spinal cord specific, co-culture platform to study ALS astrocyte/MN interactions, we were able to recapitulate previous studies 24,27,[63][64][65][66][67] showing that ALS hiPSC-A were toxic to hiPSC-MN in co-culture with several FALS and SALS lines. To identify specifically whether toxicity was mediated by the extracellular release of relevant toxic factors, we used a transwell system separating ALS hiPSC-A from hiPSC-M.…”
Section: Discussionsupporting
confidence: 72%
“…Using a fully humanized, spinal cord specific, co-culture platform to study ALS astrocyte/MN interactions, we were able to recapitulate previous studies 24,27,[63][64][65][66][67] showing that ALS hiPSC-A were toxic to hiPSC-MN in co-culture with several FALS and SALS lines. To identify specifically whether toxicity was mediated by the extracellular release of relevant toxic factors, we used a transwell system separating ALS hiPSC-A from hiPSC-M.…”
Section: Discussionsupporting
confidence: 72%
“…It has been demonstrated that astrocytes also potentially regulate neuronal proteostasis by affecting autophagic degradation pathways. The ability of conditioned medium from ALS-patient iPSC-derived astrocytes to modulate the autophagy pathway neuronal cells has been linked to the decreased expression of LC3-II and concomitant increase in the expression of SOD1 [ 132 ].…”
Section: Metabolic Dysfunction Of Astrocytes In Neurodegenerative Dismentioning
confidence: 99%
“…Astrocyte pathology is prominent, with an emerging consensus, particularly from SOD1 based studies, that astrocytes appear critical to disease progression (Papadeas, Kraig, O'Banion, Lepore, & Maragakis, 2011;Wang, Gutmann, & Roos, 2011;Yamanaka et al, 2008). It has also been shown that astrocytes derived from sporadic or familial cases can, upon co-culture or upon exposure to astrocyte conditioned media (ACM), be directly toxic to MNs leading to cell death (Cassina et al, 2008;Di Giorgio, Carrasco, Siao, Maniatis, & Eggan, 2007;Fritz et al, 2013;Haidet-Phillips et al, 2011;Kia, McAvoy, Krishnamurthy, Trotti, & Pasinelli, 2018;Madill et al, 2017;Marchetto et al, 2008;Nagai et al, 2007;Phatnani et al, 2013;Re et al, 2014;Rojas, Cortes, Abarzua, Dyrda, & van Zundert, 2014). In contrast, the influence of astrocytes on MN function is unclear and comparatively understudied.…”
Section: Introductionmentioning
confidence: 99%